Association of the Monocyte to High-Density Lipoprotein Cholesterol Ratio and Neutrophil to High-Density Lipoprotein Cholesterol Ratio With the Severity of New-Onset Coronary Artery Disease - Shu H; Han S; Qiu W; Li J; Zhang X; Su H; Wu H; Zhao G; Li Q (Journal of Inflammation Research)
Hongyun Shu,1,* Sisi Han,1,* Weiping Qiu,1 Jianhong Li,1 Xiaoyong Zhang,1 Haicui Su,1 Hongjie Wu,2 Guojun Zhao,1 Qiaowen Li3 1Department of Cardiovascular Medicine, The Affiliated Qingyuan Hospital (Qingyuan People’s Hospital) of Guangzhou Medical University, Qingyuan, Guangdong, People’s Republic of China; 2Department of Urology, The Affiliated Qingyuan Hospital (Qingyuan People’s Hospital) of Guangzhou Medical University, Qingyuan, Guangdong, People’s Republic of China; 3Institute of Gerontology, The Affiliated Guangzhou Geriatric Hospital of Guangzhou Medical University, Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiaowen Li, Institute of Gerontology, Guangzhou Geriatric Hospital, Guangzhou Medical University, Guangzhou, Guangdong, People’s Republic of China, Email Stevenxzf@sina.com Guojun Zhao, Department of Cardiovascular Medicine, The Affiliated Qingyuan Hospital (Qingyuan People’s Hospital) of Guangzhou Medical University, Qingyuan, Guangdong, People’s Republic of China, Email zhaoguojun@gzhmu.edu.cnBackground: The monocyte to high-density lipoprotein cholesterol (MHR) and neutrophil to high-density lipoprotein cholesterol ratio (NHR) are novel comprehensive indicators reflecting the body’s inflammation and lipid metabolism. Previous studies have found that MHR and NHR are associated with the risk of cardiovascular and cerebrovascular events and death. However, the correlation between MHR, NHR, and the severity of newly diagnosed coronary artery disease (CAD) has not been thoroughly explored.Methods: In this retrospective study, we enrolled 1489 patients who underwent coronary angiography for the first time between January 2022 and December 2023, of which 1143 were diagnosed with CAD. The severity of CAD was gauged by the Gensini score (GS). The relationship between MHR and NHR with CAD was validated through logistic regression analysis, adjusting for traditional cardiovascular risk factors and medication therapy. The nonlinear relationship between MHR and NHR with CAD and GS was assessed by using restricted cubic spline (RCS) models. Their independent and combined predictive effects on CAD were evaluated through receiver operating characteristic (ROC) curve analysis.Results: MHR and NHR were independently associated with CAD (both P< 0.001). In the fully adjusted model, an increase in MHR was significantly associated with an increased odds ratio (OR) for CAD (OR=4.29, 95% CI 2.72– 6.78, P< 0.001). Sensitivity analysis revealed a consistent trend (P for trend< 0.05). RCS curve analysis indicated a nonlinear relationship between the two biomarkers and GS (P< 0.05) and there were clear inflection points. The area under the curve for predicting CAD was 0.68 for MHR and 0.69 for NHR, with optimal cut-off values of 0.42 (Youden index:0.29) and 5.43 (Youden index:0.31) respectively. Combined MHR and NHR has higher predictive value.Conclusion: MHR and NHR are independently associated with CAD, and there is a nonlinear correlation with the GS. Both have some predictive value for the severity of CAD.Keywords: monocyte to high-density lipoprotein cholesterol ratio, neutrophil to high-density lipoprotein cholesterol, coronary artery disease, coronary artery disease severity, Gensini score